Two zoeal stages and the megalop of Pilumnus sluiteri De Man, 1892 [Crustacea: Brachyura: Xanthoidea: Pilumnidae] described from laboratory-reared material - Clark, P.F. (2014)
Invertebrate Reproduction and Development